EFFECT OF TOPICAL RECOMBINANT LYSOSTAPHIN AGAINST METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS INFECTION IN A MOUSE BURN WOUND MODEL - NAGALAKSHMI NARASIMHASWAMY,; INDIRA BAIRY,; SYED MUSHARRAF,; SWAPNIL KUMAR,; USHA Y NAYAK,; GAUTHAM SHENOY,; LAXMINARAYANA K BAIRY, (International Journal of Pharma and Bio Sciences, 2015)
Increased incidence of antibiotic resistant S. aureus infections has spurred the need for new antimicrobial agents. Lysostaphin is an antistaphylococcal agent, which cleaves the pentaglycine cross bridges of S. aureus cell wall leading to its lysis. Antimicrobial activity of r-lysostaphin was tested against 73 MRSA isolates by the disc diffusion assay and minimum inhibition concentration. Burn wound MRSA infected mice were treated with mupirocin and r-lysostaphin for a period of 5 days. All the MRSA isolates were sensitive to r-lysostaphin (50 µg/disc) with a zone of inhibition ranging from 14 to 17 mm and the MIC ranged between 0.25 to 2 µg/ml. The MRSA count in untreated group was 108 CFUs/g tissue. Mupirocin showed 3 log reduction (105 CFUs/g tissue) in bacterial count and r-lysostaphin significantly reduced >5 log (103CFUs/g tissue) in bacterial count as compared to the untreated group. Hence, r-Lysostaphin can be used as an effective alternative treatment for MRSA infections.